Interactional synchrony and negative symptoms: an outcome study of body-oriented psychotherapy for schizophrenia - Galbusera, Laura; Finn, Michael T.; Fuchs, Thomas (Psychotherapy research, 2018)
Objective: We sought to assess the efficacy of a manualized body-oriented psychotherapy (BPT) intervention for schizophrenia, by focusing on improvement of negative symptoms and on changes in interactional synchrony. We also explored aspects of a phenomenological theory of schizophrenia, which states that negative symptoms should be understood within an encompassing disturbance of subjectivity and intersubjectivity. Method: Sixteen persons with schizophrenia participated in 10 weeks of BPT. General psychiatric symptomatology and negative symptoms were assessed before and after therapy. Interactional synchrony was assessed via cross-correlations of movements between patient and interviewer in interviews conducted before and after therapy. Results: Psychiatric symptomatology and negative symptoms significantly improved with a medium effect size. We also demonstrated a significant increase in interactional synchrony with a strong effect size. Post hoc analyses showed a significant increase only with open-ended interviews conducted by the same interviewer. Furthermore, we explored the correlation between negative symptoms and interactional synchrony, finding a large inverse relationship. Conclusions: BPT for schizophrenia may effectively reduce patients’ negative symptoms and psychiatric symptomatology. Moreover, it may yield some recovery of pre-reflective social relations. Further evidence of the specific relation between negative symptoms and interactional synchrony would support a phenomenologically informed holistic view of schizophrenia.
Published online: 12 Aug 2016
Gesehen am 11.09.2019